2015
DOI: 10.1192/pb.bp.114.049247
|View full text |Cite
|
Sign up to set email alerts
|

ECT practices in Iraq: a national audit

Abstract: Aims and methodThis national audit examined practice of electroconvulsive therapy (ECT) in Iraq against local standards. Data were collected by a questionnaire sent to heads of departments or medical directors in the 10 Iraqi hospitals which provide ECT and by examining case notes of all patients who had ECT in the first 6 months of 2013.ResultsOf the 26 psychiatric hospitals in Iraq, 10 provide ECT. There were some resource shortcomings in the ECT clinics (e.g. only 2 had a minimum of 2 rooms and all had no E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
17
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(19 citation statements)
references
References 18 publications
1
17
1
Order By: Relevance
“…Our data showed almost equal gender distribution in patients treated with ECT; this differs from ndings in other European countries, where more female patients receive ECT [13,14]. The majority of our patients were middle aged (mean age 56), slightly younger than mean of 60 years old found in similar studies in other Western countries [15] and older than patients who received ECT in Asia and in the Middle East [16,17]. Chanpattana et al [16] proposed that this age difference in Asian ECT practice could be due to a demographic factor, and that the main indication for ECT in Asian studies is schizophrenia with more prevalence in young people.…”
Section: Discussioncontrasting
confidence: 64%
“…Our data showed almost equal gender distribution in patients treated with ECT; this differs from ndings in other European countries, where more female patients receive ECT [13,14]. The majority of our patients were middle aged (mean age 56), slightly younger than mean of 60 years old found in similar studies in other Western countries [15] and older than patients who received ECT in Asia and in the Middle East [16,17]. Chanpattana et al [16] proposed that this age difference in Asian ECT practice could be due to a demographic factor, and that the main indication for ECT in Asian studies is schizophrenia with more prevalence in young people.…”
Section: Discussioncontrasting
confidence: 64%
“…Our finding is opposite to what was found in other studies done in the region, like Iraq and Iran, with similar studies tended to be younger men with schizophrenia. 16 , 22 In this study, most of the patients in cluster two who had ECT had a primary diagnosis of schizophrenia and schizophrenia affective disorder (91.8%). In addition, > 75% who underwent ECT were treatment-resistant to medications.…”
Section: Discussionmentioning
confidence: 62%
“…This finding is similar to a study conducted in Iran and Iraq, where the main indication for ECT was the resistant treatment of schizophrenia. 16 The average number of ECT sessions received for patients in cluster two was 10.3±3.5, significantly higher than patients in cluster one. However, our finding is similar to studies by Gonzalez-Pinto et al, 23 and Krossler et al, 24 who found that the number of ECTs given per patient was 9.7±3.7 and 11.0±3.1, respectively.…”
Section: Discussionmentioning
confidence: 83%
See 2 more Smart Citations